CORPUS-CULAR-WAVE DUALISM OF LIGHT - Khushvaktov Bekmurod Normurodovich; M. Z.Nasriddinova; M. B. Nematova; N. M. Kholmuminova (American Journals, 2025)
This article highlights the importance of using innovative and interactive pedagogical technologies in teaching physics, particularly the optics section. The organization of physics education based on modern approaches allows developing students' logical and creative thinking, connecting theoretical knowledge with practice, and effectively organizing the educational process. The article also analyzes the effectiveness of the interactive method "Dividing Processes into Families" in teaching the topic "Corpuscular-Wave Dualism of Light" in the optics section.
Keywords: Physics education, optics, innovative technologies, interactive methods, the method of